ASSESSMENT OF THE AVAILABLE OBSTETRICAL RESOURCES , ALL HOSPITALS (40) IN GEZIRA STATE,SUDAN - Miskeen, Elhadi I.; Mirghani, Omer A.; Elsanousi, Mohamed; Hessian, Ali H. (مجلة الجزيرة للعلوم الصحية; مجلد 1 عدد 2 (2005), 2005)
Introduction: This study was done for the purpose of assessing the available  Obstetrical   resources (materials and human) in 40 hospitals in Gezira State, Sudan.The results were used in preparing a major health project; University of Gezira Initiative for Safe Motherhood and Childhood (UGISMC) .The aim of (UGISMC) is to reduce maternal mortality rate (MMR) and perinatal mortality rate (PMR) in Gezira State   by 50% in 5 years (2005-0210). Objectives : are to (1) assess the available delivery resources in all hospitals (40 ) in Gezira State. (2)to identify deficiencies  in the provision of obstetrical care , particular attention was given for the availability of appropriate supplies equipments , facilities and manpower. Methods : All the hospitals in Gezira State (40) were included in this descriptive observational field survey. All major theatres, minor theatres, labour rooms were visited by the principal investigator and their resources were assessed  thoroughly by direct observation, each hospital was assessed in the presence of the  medical officer in charge .The relevant information were obtained and  compared with the standard lists which were developed and prepared by a group of experts. Results : In  the 5 specialized hospitals all the obstetrical emergencies could managed safely ,namely (Madani ,Hisahisa, Alkamleen, Rufaa, and Almnagil).However, out of the 35 rural hospitals studied, in  only(11/34) 33%  emergencies could be managed safe, where the facilities are not adequate to  deal with obstetrical emergencies and maintain safe delivery . Conclusion : The majority of rural hospitals are not equipped with enough facility and man power to manage obstetric emergency.